Visualizing large-scale genomic sequences. - Glusman, G. (IEEE Engineering in medicine and biology magazine)
We discuss the GESTALT Workbench, which we have developed for large-scale genomic sequence data, with strong emphasis on the production of enriched graphical representation of the analysed data. It cam execute a variety of external analysis programs (e.g. gene recognition) as well as internal analyses (e.g. computational complexity).